Areas of proof in a discharge case (Relations Industrielles / Industrial Relations, 1960)
A discharge case involves two areas of proof; a) proof of wrong doing on the part of the grievor, and b) an evaluation of the punishment in relations to the infraction. In this case, there was cause for discipline but not for the extreme penalty of dismissal.